Supervised curricular internship in sciences and Biology: learning, challenges and motivation for teaching - Kirsch, Deise Becker; Barbosa, Maryane; Pizarro, Mariana Vaitiekunas (Revista Hipótese, 2021)
This work aims to analyze the Supervised Curricular Internship experiences of students from the Biological Sciences Degree Course of a Federal Teaching Institution. The documentary research was carried out based on the observation and conducting internship reports, in the period of 2017 to 2019. The undergraduate students’ perceptions about being a teacher were raised from the experience of the internship, emerging three categories: Learning / Positive Factors; Impasses / Difficulties; and Motivation (or not) for teaching. The data revealed the importance of the Internship as a formative moment which brings students closer to the school reality and the complex routine that involves the teaching profession.